The Role of Multimedia Platforms in Education: A Study on TikTok Usage by Generation Z - Julkarnain Julkarnain; Yusuf Hendra Pratama (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2024)
This study aims to describe the utilization of the TikTok application as an educational medium in the era of Generation Z. This research employs a descriptive qualitative method. The subjects of this study are Generation Z, with the object being the use of the TikTok application as an educational medium. Data were collected through interviews with several students of Universitas Muhammadiyah Mataram (UMMAT). The study focuses on three aspects: first, the types of TikTok content frequently viewed by Generation Z; second, the benefits of utilizing TikTok as an educational medium for Generation Z. The insights gained from this article provide a new perspective on how TikTok can be leveraged as an educational tool for Generation Z to acquire new learning knowledge and as a platform for disseminating educational content.